Awareness and knowledge of halitosis among students at two different dental universities in Turkey: a cross-sectional survey - Emine Nur Kahraman; Şehrazat Erensoy; Ahu Dikilitaş; Ayşe Gülşahı; Esra Özge Aydın; Funda Seher Özalp Ateş (BMC Oral Health)
Abstract Background Halitosis, or bad breath, significantly affects social and psychological well-being and is often caused by intraoral factors. Dentists play a key role in the diagnosis and treatment of halitosis, but inadequate education may lead to ineffective patient care. This study examines the levels of knowledge and awareness of halitosis among undergraduate dental students. Methods This study employed a cross-sectional design and used an online questionnaire that was developed via Google Forms. The questionnaire was distributed to a convenience sample of 250 undergraduate students from two different dentistry faculties who had completed their clinical internships. All the statistical analyses were performed using SPSS for Windows 11.5 (SPSS Inc., Chicago, IL, USA). Responses to the questionnaire were compared between groups using the Pearson chi-square test or Fisher’s exact test. The correct answer scores were compared between groups via the Mann‒Whitney U test. Results There was a significant difference in the degree of attention devoted to halitosis between X University and Y University (p < 0.05). When asked, “Have you ever treated patients with halitosis? “, 28.5% of fourth-year students and 60.5% of fifth-year students answered affirmatively, indicating a statistically significant difference (p < 0.001). There was no significant difference in the number of correct answers between fourth- and fifth-year students (U = 7714.00, p = 0.886). There was a significant difference in the number of correct answers between the universities (U = 5817.50, p = 0.001). The number of correct answers of X University students was slightly higher than that of Y University students. Conclusions These results support the importance of developing training programs to improve dentists’ self-confidence, social skills, and communication skills, thereby enhancing the diagnosis and treatment of halitosis. A manual for the diagnosis and treatment of halitosis could be helpful for improving dentists’ attitudes and behaviours and for promoting optimal oral health.